FORMATION STAGES OF UKRAINIAN SUFFIX SUBSYSTEM IN THE CONTEXT OF THE WORLD LANGUAGE PICTURE EVOLUTION - Kocherha, H. V. (Linguistic Bulletin (Movoznavchyi Visnyk), 2016)
The article is focused on the analysis of Ukrainian suffixation prehistory in cognitive aspect. In the most general terms, the genesis and development of Ukrainian suffix means is divided into two stages – prehistoric and historic. The first one involves Nostratic, Proto-Indo-European and Proto-Slavic levels and relates to the periods when Ukrainian did not exist as a separate language system, but its material was created within the previous language systems. The feature of these language systems, which complicates their linguistic and cognitive interpretation, lies in the fact that all of them are not attested in writing but reconstructed; and it necessarily involves more or less fragmentary character and excludes the completeness and integrity of the description; it does not allow to interpret details and the description to typical generalizations. The historical stage of Ukrainian suffixation development, particularly its substantival part, involves the evolution of language means from Kievan Rus era to the present time. There are numerous written chronicles of the language at this stage. The processes related to the specific cognitive character of suffixation were originated in prehistoric periods which continued in the history of the Ukrainian language. Thus, the denotation of passivity, substantivity, etc. by means of the formants which later became suffixes, was reconstructed in Proto-Nostratic period; the suffixes which gave the stem general and abstract semantic existed in Proto-Indo-European era and were inherited in partial or transformed form by certain Indo-European languages. The suffix lexemes of the Latin language were borrowed by Slavs in Proto-Slavic period (during the oral contacts of language speakers), and this influence lasted throughout the history of the Ukrainian language mainly in the form of literary borrowing when Latin was not a living ethnic language. The contacts were primarily in the sphere of profession and position denotations. The suffix of verbal noun was borrowed from German through Polish despite the existence of Ukrainian means for this semantics. This fact can show not only the intensive Ukrainian-Polish language contacts but also the need of such a means in the language.